Discussion on the recycling ecological chain and commercial model of decommissioned batteries. Issue 1 (March 2020) - Yin, Juanjuan; Pan, Mingyu; Chen, Zhen; Li, Jing
Abstract: When the battery capacity is reduced to less than 80%, it is no longer suitable for electric vehicles, if the decommissioned batteries directly scrapped treatment, it will cause a great waste of resources, and even cause environmental pollution. The reuse mode of lithium battery can be divided into two modes: Cascade utilization and recovery. This dissertation introduces these two methods, summarizes the current situation of power battery reuse, draws on the successful experience domestic and foreign, and combines the actual situation of domestic enterprises to improve the reuse ecosystem and business model of decommissioned batteries. The paper puts forward the business model of 'Internet + Recycling Network + specialization processing', and constructs the closed-loop network of retired power battery recovery, which integrates government supervision, enterprise operation and consumer participation.